1985
DOI: 10.1111/j.1471-4159.1985.tb08736.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Protein Content of Goldfish Optic Nerve During Degeneration and Regeneration Following Nerve Crush

Abstract: After the goldfish optic nerve was crushed, the total amount of protein in the nerve decreased by about 45% within 1 week as the axons degenerated, began to recover between 2 and 5 weeks as axonal regeneration occurred, and had returned to nearly normal by 12 weeks. Corresponding changes in the relative amounts of some individual proteins were investigated by separating the proteins by two-dimensional gel electrophoresis and performing a quantitative analysis of the Coomassie Brilliant Blue staining patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…Particular interest has been placed in identifying proteins that are induced in the ganglion neuronal cell during regeneration in this system (14,(16)(17)(18)(19)(20)(21). Some of these proteins might prove regulatory and essential for the regeneration process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular interest has been placed in identifying proteins that are induced in the ganglion neuronal cell during regeneration in this system (14,(16)(17)(18)(19)(20)(21). Some of these proteins might prove regulatory and essential for the regeneration process.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that both retinal RNA (9)(10)(11)(12) and protein (13)(14)(15) turnover increase following optic nerve axotomy. Specific retinal growthassociated proteins (GAPs) appear to be induced (16)(17)(18)(19)(20)(21), and there is a marked increase in the synthesis of constitutive cytoskeletal components, such as tubulin (14,17). Among the induced proteins, an acidic protein doublet (p68/70; pl 4.8-4.9) was detected by the in vivo labeling of newly synthesized proteins with radioactive precursors (17).…”
mentioning
confidence: 99%
“…In an attempt to unravel the molecular events associated with this regeneration (Grafstein and Murray, 1969), particular attention has been focused on the role of certain axonally transported proteins, designated "growth-associated proteins," which are transported within the fast phase of axonal transport and which show a marked increase in synthesis during regeneration (Benowitz and Lewis, 1983; Heacock and Agranoff, 1982;Perrone-Bizzozero and Benowitz, 1987). In addition, the role of certain intermediate filament proteins has also been investigated (Perry et al, 1985;Quitschke and Schechter, 1983a). These proteins are either transported along the regenerating axons within the slow phase of axonal transport or are present within the environment surrounding these axons (Deaton and Freeman, 1983;Jones et al, 1986;Perry et al, 1987;Quitschke and Schechter, 1984) and have been considered to play a role in axonal growth and plasticity of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Ganglion cells respond to nerve injury by increases in perikaryal size (Murray & Grafstein, 1969), polyribosome content (Murry & Forman, 1971;Whitnall & Grafstein, 1983), RNA content (Murray, 1973), and protein synthesis (Heacock & Agranoff, 1976;Burrell et al, 1978;Perry et al, 1987). Proteins with the same characteristics as GAP-43 have since been reported in regenerating optic nerves of the goldfish (Benowitz et al, 1981;Heacock & Agranoff, 1982;Benowitz & Lewis, 1983;Perry et al, 1985). These proteins have been referred to as growth association proteins (GAPs), an example of which is the 43 kD protein from toad optic nerves, which increased during optic nerve regeneration (Skene & Willard, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…These studies point to a role for laminin in optic nerve regeneration (Hopkins et al, 1985 studies have shown a response by non-neuronal cells during regeneration that includes an increased release of proteins during regeneration (Arenander & DeVellis, 1981; Perry et al, 1985;Schwartz et al, 1985;Freeman et al, 1986;Bawnik et al, 1987). These studies point to a role for laminin in optic nerve regeneration (Hopkins et al, 1985 studies have shown a response by non-neuronal cells during regeneration that includes an increased release of proteins during regeneration (Arenander & DeVellis, 1981; Perry et al, 1985;Schwartz et al, 1985;Freeman et al, 1986;Bawnik et al, 1987).…”
Section: Introductionmentioning
confidence: 99%